Radiographic findings and pathology of a dog with mercury toxicity. (December 2020) - Chung, Cheng-Shu; Li, Yi-Chia; Lin, Lee-Shuan
Highlights: A young dog was found with an open wound and a used syringe and needle nearby. The dog presented with tetraplegia, lethargy, and abnormal joint articulation. Imaging findings of intentional mercury poisoning in a dog, confirmed by necropsy. Heavy metal intoxication can affect metaphyses and physes in growing animals. Abstract: Here, we describe radiographic findings of mercury toxicity followed by a forensic necropsy in a young dog. A young female dog presented for evaluation of progressive tetraplegia over the course of two weeks. Non-ambulatory tetraplegia was noted with normal deep pain sensation and cranial nerve reaction. Radiographic examination revealed spotty metal opaque materials spreading at the subcutis of the back, radiolucent zones at the metaphyses of long bones and in the vertebral skeleton, and joint-centered radiolucency in the elbow and hip joints. The dog was not responsive to surgical treatment and died the next day. Necropsy and toxicological examination confirmed mercury toxicity-associated bony changes in this dog. This case is the first report describing the radiographic findings of bony changes associated with mercury intoxication and showed that heavy metal intoxication affects metaphyses and physes in growing animals.